HUBUNGAN DUKUNGAN KELUARGA DENGAN PERAWATAN DIRI PASIEN ODGJ (ORANG DENGAN GANGGUAN JIWA) DI WILAYAH KERJA PUSKESMAS RASIMAH AHMAD BUKITTINGGI TAHUN 2022 - Falerisiska Yunere (PREPOTIF : JURNAL KESEHATAN MASYARAKAT, 2022)
HUBUNGAN DUKUNGAN KELUARGA DENGAN PERAWATAN DIRI PASIEN ODGJ (ORANG DENGAN GANGGUAN JIWA) DI WILAYAH KERJA PUSKESMAS RASIMAH AHMAD BUKITTINGGI TAHUN 2022 Falerisiska Yunere1, Oriza Sativa2, Yendrizal Jafri3 Email : falemorin@yahoo.com ABSTRACT Riskesdas 2018 data shows the prevalence of mental emotional disorders as indicated by symptoms of depression and anxiety for ages 15 years and over reaches around 6.1% of the total population of Indonesia. The prevalence of mental disorders has increased the proportion of mental disorders including schizophrenia in Indonesia which was quite significant in 2018 compared to 2013. Families must provide support in self-care of ODGJ patients, so that ODGJ patients can fulfill their self-care. The purpose of this study was to determine the relationship between family support and self-care for ODGJ patients in the Work Area of ??the Rasimah Ahmad Health Center in 2022. This research method was a quantitative study with total sampling. The sample in the study was the entire population of 44 ODGJ families. In this study, the data were processed using the chi-square test. The results showed that from 38 respondents who had good family support there were 34 (89.5%) respondents who had good self-care, there were 4 (10.5%) who had poor self-care, while from 6 respondents who had family support there are less than 1 person (16.7%) of respondents who take good care of themselves, there are 5 people (83.8%) of respondents who lack self-care. This study using the chi-square test, the results obtained P value = 0.001, it can be concluded that there is a relationship between family support and self-care for ODGJ patients. It is hoped that this study will encourage families, communities and health workers to motivate the patient's family on the importance of family support with self-care for ODGJ patients